The bastards of Euripides: illegitimacy in the Hippolytus, the Andromache, and the Ion - Sülter, James Nicholas Edwin (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
The Pericles Citizenship Law of 451 made citizenship contingent on an individual man having Athenian blood on both his father and mother's side. Men with foreign mothers were denied any rights to the key institutions that conferred Athenian belonging, such as deme and phratry membership, as well as, of course, citizenship. When, however, the Peloponnesian War began in 431, the population of Athenian citizens was quickly diminished by military conflict and plague and they sought a solution to repopulate their numbers with as little change to the original law as possible. The result was an amendment in 429 allowing citizens with no living legitimate (Î³Î½Î®ÏƒÎ¹Î¿Î¹) heirs to legitimise their bastards (Î½ÏŒÎ¸Î¿Î¹) in their place. A year after this, Euripides wrote the Hippolytus, a play that deals very closely with the issues of bastardy, bastards' place in the polis and the oikos, and their treatment by those who are legitimate. As the war went on, he proceeded to produce two other plays containing bastard characters, the Andromache (c.425) and the Ion (c.413), in which he similarly explored the consequences of illegitimacy. In all three plays his attitude towards bastards is overwhelmingly sympathetic and the way he chooses to present their situations suggests his disagreement with the arrogance and antipathy that continued to push many of these often very worthy individuals to the fringes of society. This thesis seeks to examine Euripides' presentation of bastards through a close reading of the relevant texts, in order to understand how the plays reacted to the contemporary circumstances of and what comments they are making.
Keywords: Euripides; Euripides -- Criticism and interpretation; Euripides -- Hippolytus; Euripides -- Andromache; Euripides -- Ion; Illegitimacy in literature; Tragedy -- History and criticism; Citizenship in literature